Mental Health and Resilience in Nursing Students: A Longitudinal Study - Martinez, William Donegá; Casaleiro, Tiago; de Souza Menezes, João Daniel; da Silva, Matheus Querino; dos Santos, Emerson Roberto; Franco, Rauer Ferreira; Quiterio, Alex Bertolazzo; de Barros, Thales Guardia; de Deus Silva, Ana Julia; Lopes, Luiz Otávio Maciel; Lopes, Sônia Maria Maciel; de Arnaldo Silva Rodriguez Castro, Natalia Almeida; et al. (MDPI, 2025)
Mental health challenges are increasingly prevalent among young individuals, particularly within high-stress academic environments such as nursing education. Resilience is critical for maintaining well-being and adapting to university demands. OBJECTIVE: To assess resilience levels in first-year nursing students at FAMERP (Faculty of Medicine of São José do Rio Preto) upon entry in 2021 and their longitudinal evolution in 2022 and 2023, using the Wagnild and Young Resilience Scale. The study also aims to explore the implications for mental health promotion in young healthcare professionals. METHODS: A descriptive, longitudinal, prospective, and quantitative study was conducted with 40 students. Data collection was performed via electronic forms and analyzed using descriptive statistics and specific tests within the R programming language. RESULTS: The predominantly female sample, with a mean age of 19.5 years, exhibited moderate to high resilience levels: mean scores of 132.5 (2021), 135.8 (2022), and 139.2 (2023). A significant reduction in the Perseverance factor (p = 0.0131) was noted. There was a positive correlation between age and resilience scores (r = 0.42; p < 0.01). DISCUSSION: Despite a slight overall increase in resilience, the decline in Perseverance is concerning, indicating potential growing mental health challenges as students progress. Small age differences significantly influence mental health outcomes. This decline may be related to increased academic stress, exposure to emotionally challenging clinical situations, and the cumulative effects of the "costs of caring". CONCLUSIONS: Nursing students exhibit promising resilience levels, yet there is a critical need for interventions targeting Perseverance to enhance academic performance and patient care quality. Social Impact: This study contributes to the development of educational strategies designed to promote resilience, thereby potentially improving the mental health and academic performance of nursing students. By focusing on mental well-being, a more resilient healthcare workforce can be cultivated and better prepared to meet systemic challenges.